Analisis Luaran Radiasi Perangkat Sinar-X dengan Sumber Tabung Vakum Gammatron 2x2A - Samuel Gideon; Taat Guswantoro (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2019)
An x-ray experiments require sophisticated and advanced apparatus which is very expensive resulting some laboratories in universities have not been able to accommodate these stuffs. In fact, a simple and homemade X-ray apparatus may be designed easily and it is quite cheap even the rill x-ray apparatus that equipped by many vendors. Basically, x-ray is generated from x-ray tube following two mechanisms which are characteristics x-ray and Bremstrahlung x-ray. In this study, we designed a simple x-ray apparatus which may generate Bremstrahlung x-ray. The designed simple x-ray apparatus consists of 2x2A rectifier vacuum tube and 25 kV high voltage power supply. For radiation protection and dosimetry, we conducted the experiment in a lead-shielded bunker and used Unfors Raysafe X2 as well as Digilert 100 surveymeter. We measured background radiation dose of 0,49 Î¼Gy/h. From the designed simple x-ray testing experiment, we measured radiation dose of 0,49 Î¼Gy/h Keywords : 2x2A rectifier vacuum tube, high voltage power supply, simple x-ray apparatus